Gamifying sustainability: creating an app to promote SDG practices among students - Mohd Yusof, Noorlailahusna; Ahmad Khan, Hafizah Hammad; Ahmad Zawawi, Azlyn (2025)
Despite widespread awareness of the United Nations' Sustainable Development Goals (SDGs) among students, with 92% of surveyed students demonstrating familiarity, a disconnect remains between knowledge and consistent sustainable practices. This project addresses this gap through an innovative gamified mobile app designed to transform SDG education into an engaging, habit-forming experience. Building on survey results showing that 89% of students favour gamified learning, the app employs behavioural psychology principles through daily challenges with progress tracking, AR mini-games, social leaderboards, and real-world impact dashboards to incentivise sustainable actions such as recycling and energy conservation. By merging education with interactive gameplay, the initiative aims to increase student engagement with SDGs by 50% while fostering measurable behaviour change. Future development plans include school partnerships for curriculum integration, amplifying the app's potential to redefine sustainability education as a dynamic, student-driven process that empowers youth as active change agents for a sustainable future, perfectly aligning with the competition's theme of 'Transforming Education.